World Trends in Evaluating the Activities of Professors and Teachers in Foreign Higher Education Institutions - D.Sh.Jo’rayeva, Ruzmatov J.A (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the ever-evolving landscape of higher education, the evaluation of professors and teachers in foreign institutions plays a pivotal role in maintaining academic standards, fostering innovation, and ensuring the quality of educational outcomes. This article explores global trends that shape the evaluation processes of faculty members across international higher education institutions, highlighting key factors, challenges, and implications for educators and institutions alike.